2021
DOI: 10.3889/oamjms.2021.6464
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Awareness, and Attitudes toward Umbilical Cord Blood Biobanking

Abstract: BACKGROUND: Umbilical Cord Blood (UCB) stem cells are a non-invasive, effective alternative source of hematopoietic stem cells for the treatment of a variety of diseases. AIM: The aim of the study was to research knowledge, awareness, and attitudes of the general public and health professionals regarding the UCB storage. MATERIALS AND METHODS: A cross-sectional study was conducted with an online survey (n = 408) using the snowball method. RESULTS: A majority of respondents declared that they were not awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…This accords with other studies showing that a majority of respondents acquired their information from medical experts [ 12 , 15 ]. By contrast, this result does not agree with a study showing that only 15% of respondents obtained their knowledge from health experts, with the majority receiving it from social media [ 29 ]. The other results are as follows: 25.45% (n=98) received no information or education, 23.64% (n=91) obtained it from the internet or social media, 12.73% (n=49) from family or friends, and only 10.91% (n=42) from educational institutions.…”
Section: Discussioncontrasting
confidence: 99%
“…This accords with other studies showing that a majority of respondents acquired their information from medical experts [ 12 , 15 ]. By contrast, this result does not agree with a study showing that only 15% of respondents obtained their knowledge from health experts, with the majority receiving it from social media [ 29 ]. The other results are as follows: 25.45% (n=98) received no information or education, 23.64% (n=91) obtained it from the internet or social media, 12.73% (n=49) from family or friends, and only 10.91% (n=42) from educational institutions.…”
Section: Discussioncontrasting
confidence: 99%
“…Some prior studies from Middle Eastern countries recommended creating awareness, educating, and counseling women about stem cell donation and cord blood donation [26,27]. A study from Slovenia also reported that people from the general population were not aware of UCB banking [28]. A study of pregnant women from Italy tested the theory of planned behavior to identify the social and psychological elements of women's decision to donate cord blood.…”
Section: Introductionmentioning
confidence: 99%